Pengaruh Komposisi Bahan Baku Terhadap Mutu Sensoris Kerupuk Gurita (Octopoda) - Isni, Sanita (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Octopus has the potential as a raw material for processing food products, including octopus crackers which have a distinctive taste and are rich in protein. A study has been conducted with the aim of calculating the yield of octopus cracker processing with variations in octopus percentage, and analysing the level of consumer preference for octopus crackers with variations in octopus percentage. The study was conducted using a factorial design with 5 treatment variations, namely octopus percentage of 10%; 20%; 30%; 40% and 50%. The analysis was carried out on octopus crackers consisting of yield analysis and organoleptic tests using 20 fairly trained panellists to test the level of preference for colour, aroma, and texture parameters. The results showed that the yield of octopus cracker processing ranged from 38.35 - 42.17%. The level of panellist preference for the colour parameter ranged from 3.6 - 4.4 (like), 3.55 - 4.10 (like) for the aroma parameter, and 3.6 - 4.2 (like) for the texture parameter.